Characteristics of Long-run Return and Risk: A Unified Performance Metric. Issue 2 (1st April 2017) - Cheng, Ping; Lin, Zhenguo; Liu, Yingchun
Abstract: It is well documented in the literature that long-run asset prices do not follow a random walk, thus their returns are not independent and identically distributed (i.i.d.) over time. But how can this notion—long-run returns and volatilities being horizon dependent—be incorporated into formal pricing models? In this paper, we develop a unified risk-adjusted return metric that is applicable to both private assets and public securities. Since such metric is based on a pair of empirically determined return and risk characteristic lines that depict the horizon impact on return and volatility, our performance metric is rooted in empirical evidence rather than assumptions. The results suggest that long-run asset performance cannot be adequately measured by single-period return and volatility. Rather, prudent long-run investment decisions must include careful consideration of the anticipated holding period and a proper understanding of the long-run return and risk characteristics.